Pemantauan Sampah Pantai Di Kawasan Wisata Pantai Labu Sawo, Kabupaten Sumbawa - Astriana, Baiq Hilda; Putra, Aryan Perdana; Arlina, Baiq Fadila (Universitas Mataram, 2025)
Marine debris, especially plastic waste in coastal areas, poses a significant threat to the sustainability of marine ecosystems and the livelihoods of communities that depend on them. Labu Sawo Beach in Sumbawa Regency, known as a strategic area with promising ecotourism potential, is currently facing issues related to coastal waste. As a form of community engagement, a service program was carried out with the aim of educating young people to become more aware of and actively involved in monitoring coastal waste. The methods used in this activity included the delivery of training materials, demonstrations of coastal waste monitoring techniques, and evaluations of the participants' understanding. The monitoring results generally indicated that Labu Sawo Beach is experiencing a serious waste accumulation problem, caused by its geographical location, increasing tourism activities, and waste carried through river streams. Furthermore, participants' understanding of the training materials significantly improved, with an average evaluation score increase of 95.73%. This activity demonstrates the crucial role of youth involvement. With proper training, they may become the front line in efforts to manage coastal waste in a more sustainable and data-driven manner